2016
DOI: 10.3390/en9060464
|View full text |Cite
|
Sign up to set email alerts
|

Interdependencies between Biofuel, Fuel and Food Prices: The Case of the Brazilian Ethanol Market

Abstract: Abstract:Brazil is currently the world's largest sugar producer and exporter, as well as the world's largest producer and consumer of sugarcane ethanol as a transportation fuel. The growth of this market originates from a combination of government policies and technological change, in both the sugarcane ethanol processing sector and the manufacture of flex-fuel vehicles. In recent years however, ethanol production has been questioned due to its possible impact on food prices. The present paper aims to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…In this regard, a recent contribution evaluated the LCA of algae production using a stochastic model [45]. The results were then compared with those of other agricultural crops, such as savoy cabbage and corn, and indicated that conventional crops had a lower environmental impact than algae, in terms of energy consumption, greenhouse gas emissions, and water, regardless of the place of cultivation [45].…”
Section: Other Annual Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, a recent contribution evaluated the LCA of algae production using a stochastic model [45]. The results were then compared with those of other agricultural crops, such as savoy cabbage and corn, and indicated that conventional crops had a lower environmental impact than algae, in terms of energy consumption, greenhouse gas emissions, and water, regardless of the place of cultivation [45].…”
Section: Other Annual Plantsmentioning
confidence: 99%
“…The results were then compared with those of other agricultural crops, such as savoy cabbage and corn, and indicated that conventional crops had a lower environmental impact than algae, in terms of energy consumption, greenhouse gas emissions, and water, regardless of the place of cultivation [45]. On the other hand, algae have positive impacts in terms of the total use of agricultural land and potential eutrophication.…”
Section: Other Annual Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both factors contribute to Brazilian's position as the world's largest sugar producer and exporter, and an important producer and consumer of ethanol (Adami et al, 2012;Bentivoglio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The literature about Brazilian commodities futures markets is still little explored (Serra et al 2011;Bentivoglio et al 2016), notwithstanding the importance of agribusiness to the country's economy. A purpose of this study is to examine the relationship between ethanol spot and futures prices in Brazil.…”
Section: Introductionmentioning
confidence: 99%